2021
DOI: 10.1177/02841851211024002
|View full text |Cite
|
Sign up to set email alerts
|

The value of dynamic contrast-enhanced magnetic resonance imaging combined with apparent diffusion coefficient in the differentiation of benign and malignant diseases of the breast

Abstract: Background The value of combined dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and apparent diffusion coefficient (ADC) histogram analysis for the diagnosis of breast cancer has not been evaluated in previous studies. Purpose To investigate the diagnostic value of DCE-MRI combined with ADC in benign and malignant breast lesions. Material and Methods The clinicopathological imaging data included 168 patients (177 lesions) with breast lesions who underwent convention breast MRI, DCE-MRI, and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Furthermore, Sohrab et al found that plateau and washout DCE curve types were associated with malignancy 34 . Similarly, the proportion of plateau/washout DCE curve types in the non‐pCR group was significantly higher 35,36 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, Sohrab et al found that plateau and washout DCE curve types were associated with malignancy 34 . Similarly, the proportion of plateau/washout DCE curve types in the non‐pCR group was significantly higher 35,36 …”
Section: Discussionmentioning
confidence: 97%
“…34 Similarly, the proportion of plateau/washout DCE curve types in the non-pCR group was significantly higher. 35,36 Data are expressed as the mean ± standard deviation or n (%), and p < 0.1 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion-weighted imaging (DWI) has become clinically relevant (12,13). DWI is a non-invasive MRI technique that can measure the diffusion of water molecules across tissues, in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a bi-exponential model is necessary to measure diffusion and microperfusion parameters. ADC values may be determined in three different types of tumor regions of interest (ROIs), including a circular ROI (ROI-c), single-slice ROI (ROI-s), and whole-tumor ROI (ROI-w) (13). ADC values can provide objective and accurate quantitative information (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%